DEVELOPMENT OF ANDROID-BASED AUGMENTED REALITY (AR) ON CRYSTAL STRUCTURE MATERIALS (Universitas Pendidikan Indonesia, 2024)
Interesting learning media can arouse students' interest in learning so that it is easy to understand. Students will gain more concrete knowledge through direct experience, through artificial objects, interactive media, virtual reality media and augmentation. Augmented reality (AR) as a learning medium can create a deeper learning experience through clear visual representation. This research uses a quantitative descriptive approach with the RD Planning, Production and Evaluation (PPE) model according to Richey and Klein. This PPE model is used as an analytical model from the beginning to the end of the research (Sugiyono, 2015). The Android-based Augmented reality (AR) application on crystal structure material was created using Unity 2021 software, with 3 other supporting software. The application has brief content along with augmented reality features of BCC, FCC and HCP crystal structures. The percentage of suitability of material experts for Android-based Augmented reality (AR) applications on crystal structure material is 89.4%. The percentage of suitability of media experts for Android-based Augmented reality (AR) applications on crystal structure material is 89.3%. The results of this application development are in the